Pengaruh Profitabilitas, Solvabilitas Dan Financial Distress Terhadap Audit Delay Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2017-2021 - Silalahi, Indah Permata Sari (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to determine the effect of Profitability, Solvency, Financial Distress, on Audit Delay with Company Size as a moderation variable in Manufacturing Companies listed on the IDX in 2017-2021. The Moderated Regression Analysis (MRA) design is used to examine the causal relationship between the independent variable and the dependent variable which is strengthened or weakened in the presence of a moderating variable. This type of research is quantitative. The samples used 44 companies. The results showed that Profitability, Solvency and Financial Distress had a significant effect on Audit Delay. Using Company Size as a moderating variable, shows that Company Size is able to moderate the relationship of Profitability variables to Audit Delay but is unable to moderate the relationship of Solvency and Financial Distress to Audit Delay.